Paul's Theology: Consistent or Inconsistent? - Beker, Johan Christiaan (New Testament studies, 1988)
. Recent discussions of Paul's theology have reached a virtual consensus that Paul is not a dogmatic theologian, but rather an interpreter of the gospel. In this light we would expect that the tendencies of the history of Christian thought to discover a dogmatic ‘Mitte’, from which all other elements of his thought can be deduced, would have ceased. And yet the immense dogmatic pressure of the Christian tradition still persists: with their search for ‘die Mitte’ of Paul's thought which they locate in justification by faith and/or in the righteousness of God, both Barth and Käsemann show that the dogmatic quest of the church from the time of Augustine to Luther and Calvin is still alive.